Гормональна активність жирової тканини та кластери метаболічного синдрому в осіб з ожирінням на тлі формування інсулінорезистентності - Ларін, О. С.; Кирилюк, М. Л.; Третяк, О. Е.; Черенько, М. С.; Щекатурова, Л. В.; Дашук, Т. І. (Clinical Endocrinology and Endocrine Surgery, 2013)
The level of blood lipocytokines in obese patients according to the degree of insulin resistance (IR) showed that the content of leptin was significantly greater in patients with normal HOMA-IR, or indicates the protective role of this cytokine with respect to the formation of IR in patients with elevated body weight, or indicates ambiguity role of leptin in the development of IR in obese individuals. This fact indicates that elevated levels of leptin in the blood is not always a prerequisite and/or criteria of metabolic syndrome in obese patients, since, according to our research does not always increase the level of leptin in the blood leads to the degree of IR. The data obtained from the concentration of leptin in the blood correlate with the decrease of adiponectin concentration in blood of patients with an index above 2.7 as compared to patients without IR.